Analysis of Learning Obstacles in the Metapedadidactic Stage of the System of Linear Equations in Two Variables (SLETV) - Maulana Al Aziz Harahap; Tatang Herman; Aan Hasanah (Universal Education, 2025)
This study aims to identify and analyze various learning obstacles encountered by eighth-grade students in understanding the topic of systems of linear equations in two variables (SLETV), using the Didactical Design Research (DDR) approach at the metapedadidactic stage. Employing qualitative methods, data were collected through diagnostic pretests and posttests, classroom observations, and in-depth interviews. The findings reveal that students face three types of learning obstacles: ontogenic, didactic, and epistemological. Ontogenic obstacles are related to difficulties in understanding algebraic symbols and representing problems within real-life contexts, while didactic obstacles arise from teacher-centered instructional methods and insufficient supporting materials. Epistemological obstacles are evident in students’ inability to apply conceptual knowledge when confronted with non-routine problems. Through DDR-based interventions—comprising prospective, metapedadidactic, and retrospective analyses—these learning barriers can be reduced, resulting in significantly improved student understanding, as reflected in enhanced learning outcome indicators. These findings highlight the importance of early detection of learning obstacles and the use of reflective practices during the metapedadidactic stage as a foundation for designing more adaptive mathematics teaching strategies that are aligned with students’ needs.